Perancangan Pemanfaatan Pompa Air Tenaga Surya Untuk Sumber Air Bersih Desa Sukarame, Kec. Sajira, Banten - Yoakim Simamora (Sekolah Tinggi Teknik - PLN, 2020)
Water requirements for the people in sukarame village, Sajira, for daily needs in the dry season tend to increase, They always experience drought for 6-9 months annually. The people independently built water reservoirs from mountain water sources. Water is pumped using a water pumping machine and accommodated in reservoirs, then distributed to local residents through pipes with minimum distribution distance is 1 km from the reservoir. Because the distance between water sources and the people complaining about clean water does not reach their homes. This problem can be done by building a ground well located not far from the house of the community, so that the distance between the source of clean water and the house of the community is not too far, water from the water source will be accommodated in reservoirs by sucking ground water using a solar water pump so residents are not burdened with electricity fees to suck ground well water into clean air tendons. This design is expected to provide a solution for clean water sources for volunteers in the village of Sajira.